Examining the Influence of Profitability and the ASEAN Corporate Governance Scorecard on Tax Avoidance in Indonesian Banking Companies - Putri, Adelia Haryanto; Dewi, Siti Ratna Sari (Manunggal Halim Jaya, 2026)
This study investigates the effect of profitability and the ASEAN Corporate Governance Scorecard (ACGS) on tax avoidance, both partially and simultaneously, in banking sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Profitability is proxied by Return on Assets (ROA), ACGS represents good corporate governance practices, and tax avoidance is measured using the Effective Tax Rate (ETR). The study employs secondary data obtained from annual financial reports, selected through purposive sampling, and analyzed using multiple linear regression with EViews 12. The results reveal that profitability has a significant negative effect on tax avoidance (p < 0.05), indicating that more profitable firms tend to minimize their tax burden through avoidance practices. Meanwhile, the ASEAN Corporate Governance Scorecard (ACGS) shows a positive but insignificant effect (p > 0.05), suggesting that the implementation of corporate governance has not yet effectively mitigated tax avoidance behavior. Simultaneously, profitability and ACGS significantly influence tax avoidance, with an adjusted R² of 12.1%, meaning other factors beyond these variables also play a role. These findings reinforce the relevance of Agency Theory and Positive Accounting Theory, confirming that managerial incentives and governance mechanisms shape firms’ tax decisions. Practically, this study highlights the need for regulators to strengthen governance enforcement and for companies to improve transparency to enhance compliance and reduce aggressive tax practices.